Outcome of paracetamol poisoning after treatment with intravenous or oral N-acetylcysteine. - Thapa, Raj Kumar; KC, Kanchan; Khatri, Rishi; Deo, Rajeeb; Sharma, Arun; KC, Indu (Medical Journal of Shree Birendra Hospital, 2017)
Introduction: Paracetamol (PCM) is one of the most common drug in clinical practice and it is generally safe for use at recommended doses. However, its overdose can cause mild hepatotoxicity to severe hepatic necrosis and even hepatic failure. N-acetylcysteine (NAC) is the standard recommended antidote for PCM poisoning which is available in both intravenous (IV) and oral formulations. This study aimed to measure outcome in PCM poisoning after treatment with oral or IV NAC.Methods: A descriptive cross-sectional study was conducted in randomly selected 50 consecutive patients presented within 72 hours of PCM poisoning. Comparative outcomes measured in correlation of dynamics of liver enzymes alanine aminotransferase, aspartate aminotransferase and prothrombin time along with development of adverse drug reactions and clinical cure rate. Comparison of categorical variables by Chi-square test and Fisher's test and the comparison of mean between groups by Student's t-test with p-value